2018
DOI: 10.1111/1346-8138.14355
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Dermatological Association Guidelines: Guidelines for the treatment of acne vulgaris 2017

Abstract: The Guidelines for the Treatment of Acne Vulgaris of the Japanese Dermatological Association was first published in Japanese in 2008 and revised in 2016 and 2017. These guidelines (GL) indicate the standard acne treatments in Japan and address pharmaceutical drugs and treatments applicable or in use in Japan. In these GL, the strength of the recommendation is based on clinical evidences as well as availability in Japanese medical institutions. In the 2016 and 2017 GL, some of the clinical questions were revise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 171 publications
(246 reference statements)
0
63
0
1
Order By: Relevance
“…Since the increase in antibiotic resistance became a major public concern, many acne treatment guidelines have encouraged the stewardship of antibiotic use . Topical antibiotics should be used in a limited setting and for a restricted duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the increase in antibiotic resistance became a major public concern, many acne treatment guidelines have encouraged the stewardship of antibiotic use . Topical antibiotics should be used in a limited setting and for a restricted duration.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatologists are among the physicians most commonly prescribing antibiotics in the USA, and acne vulgaris (AV) is the most common indication . As a result, antibiotic stewardship has been strongly encouraged in several guidelines during the last few years …”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, antimicrobial agents are used for acne treatment against C. acnes . However, a heavy use of antibiotics causes an increase in bacterial resistance, limiting the continued use of antimicrobial treatment for acne . Some natural medicines with antimicrobial and antipathogenic activity have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Kampo medicines, traditional Japanese herbal medicines, have been used for acne treatment. Of these, Keigairengyoto, Seijoboufuto and Jumihaidokuto are considered as one of the options in acne treatment guidelines . However, there is no current understanding regarding the mechanism by which these medicines contribute to acne treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Of all antimicrobial agents, the amount of quinolone use is the third highest after that of macrolides and ÎČ‐lactams . In particular, topical nadifloxacin and ozenoxacin and oral levofloxacin are used for treatment of skin diseases such as acne vulgaris . We previously reported that the antimicrobial resistance of Cutibacterium (formerly Propionibacterium ) acnes isolated from acne patients is affected by antimicrobial use .…”
Section: Introductionmentioning
confidence: 99%